Analisis Risiko Kecelakaan Kerja Dengan Metode Failure Mode and Effect Analysis (FMEA) Pada Operasional Gudang di Perusahaan Logistik Cibitung - Farras, Muhammad Dhiya (Proceeding Mercu Buana Conference on Industrial Engineering, 2020)
PT XYZ is a company engaged in logistics and warehousing services. The number of work accidents at PT XYZ incrased from 2019 to 2021. The study aims to identify the risk of work accidents and determine control. The FMEA method is used to identify hazards and risk priority in RPN form. The highest RPN value is the process of picking goods from the storage location/rack to the staging area (picking process) with a value of 291.33. Risk control needs to be carried out based on control hierarchy such as elimination, substitution, engineering, administration, and PPE.